Effect of hot water immersion on acute physiological responses following resistance exercise - Jackman, Joshua S.; Bell, Phillip G.; Van Someren, Ken; Gondek, Marcela B.; Hills, Frank A.; Wilson, Laura J.; Cockburn, Emma (Frontiers in Physiology, 2023)
Hot water immersion (HWI) is a strategy theorised to enhance exercise recovery. However, the acute physiological responses to HWI following resistance exercise are yet to be determined.The effect of HWI on intramuscular temperature (IMT), muscle function, muscle soreness and blood markers of muscle cell disruption and inflammatory processes after resistance exercise was assessed. Sixteen resistance trained males performed resistance exercise, followed by either 10 min HWI at 40℃ or 10 min passive recovery (PAS). Results Post-intervention, the increase in IMT at all depths was greater for HWI compared to PAS, however this difference had disappeared by 1 h post at depths of 1 and 2 cm, and by 2 h post at a depth of 3 cm. There were no differences between groups for muscle function, muscle soreness or any blood markers. Conclusion These results suggest that HWI is a viable means of heat therapy to support a greater IMT following resistance exercise. Recovery of muscle function and muscle soreness is independent of acute changes in IMT associated with HWI.